2016
DOI: 10.1371/journal.pone.0165515
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Plasmodium falciparum Molecular Markers of Antimalarial Drug Resistance in a Residual Malaria Focus Area in Sabah, Malaysia

Abstract: Chloroquine (CQ) and fansidar (sulphadoxine-pyrimethamine, SP) were widely used for treatment of Plasmodium falciparum for several decades in Malaysia prior to the introduction of Artemisinin-based Combination Therapy (ACT) in 2008. Our previous study in Kalabakan, located in south-east coast of Sabah showed a high prevalence of resistance to CQ and SP, suggesting the use of the treatment may no longer be effective in the area. This study aimed to provide a baseline data of antimalarial drug resistant markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Results from this study are consistent with another study from Sabah, which reported only wild-type kelch13 molecular markers using 17 SNPs from 50 P. falciparum isolates collected from 2008 to 2014 [ 30 ]. The absence of P. falciparum artemisinin drug resistance in Malaysia, either spread from imported cases from neighbouring countries harbouring resistant P. falciparum parasites, or de novo resistance arising independently, is likely due in large part to the effective Malaysian malaria public health programme [ 25 ].…”
Section: Discussionsupporting
confidence: 90%
“…Results from this study are consistent with another study from Sabah, which reported only wild-type kelch13 molecular markers using 17 SNPs from 50 P. falciparum isolates collected from 2008 to 2014 [ 30 ]. The absence of P. falciparum artemisinin drug resistance in Malaysia, either spread from imported cases from neighbouring countries harbouring resistant P. falciparum parasites, or de novo resistance arising independently, is likely due in large part to the effective Malaysian malaria public health programme [ 25 ].…”
Section: Discussionsupporting
confidence: 90%
“…The existence and importance of this reservoir could only be uncovered by a molecular method. Molecular surveillance of specific polymorphisms was also used to demonstrate high degrees of susceptibility (61, 70, 73, 87), sustained resistance (60) or high risk for resistance (89) in specific countries. In each case, ongoing molecular surveillance is suggested as an early warning mechanism for the arrival or development of resistance.…”
Section: Application Of Molecular Techniques To the Epidemiology Of Ementioning
confidence: 99%
“…It is in borders with Malaysia to the south and Myanmar to its upper west. In Malaysia, the incidence of malaria is estimated to be 13 cases per 100,000 populations [26] and the prevalence of antimalarial drug resistance was relatively low [27]. The molecular analysis showed a single copy of Pfmdr1 and wild-type PfKelch13 genes indicating that Malaysia has limited case of artemisinin resistance.…”
Section: Introductionmentioning
confidence: 99%